Adaptive Model Simplication For Level Of Detail In Real-Time Rendering - Ng, Kok Why (2005)
The main focus of this thesis is to improve the existing simplification methods in terms of the computation efficiency and visul fidelity, and to approach the proposed methods to adapt to the user's response. We have done a through survey on the existing simplification methods. We use Half-edge Collapse Transformation Method to collapse the candidate edges.